CRYPTIC MARINE BIODIVERSITY OF RAJA AMPAT ISLANDS - Hoeksema, Bert W.; Tuti, Yosephine; Suharsono, - (Marine Research in Indonesia, 2009)
During a marine field survey in Raja Ampat as part of Ekspedisi Widya Nusantara (E-win), 21 scientists, studied the areas cryptic biota on coral reefs and in marine lakes. Cryptic species lead hidden lives due to their small size, successful camouflage or mimicry, or because they live in habitats that are easily overlooked or hard to access. Hundreds of species were sampled, many of which still have to be identified. The species richness of Raja Ampat appears to be very high, even among other areas within the centre of maximum marine biodiversity, the so-called Coral Triangle.